2015
DOI: 10.1007/s13744-015-0281-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution, Temporal Variation and Specificity of Microhabitat of Tropisternus Species (Coleoptera: Hydrophilidae) in Permanent Ponds

Abstract: The spatial distribution and temporal variation of 11 species of Tropisternus were analyzed in two permanent ponds located in the province of Corrientes, Argentina. Samples were collected every 15 days, between October 2010 and March 2011. The species recorded were Tropisternus collaris (Fabricius), Tropisternus ovalis Castelnau, Tropisternus laevis (Sturm), Tropisternus lateralis limbatus (Brullé), Tropisternus longispina Fernández & Bachmann, Tropisternus carinispina Orchymont, Tropisternus bourmeisteri Fern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The respiratory demands of some of these genera may be satisfied by a thin layer of air maintained along their body surface (plastron), which makes regular ascents to the water surface, and some others have a respiratory siphon to intake atmospheric oxygen. Gómez Lutz et al (2015) found that the habitats and microhabitats (forming by different species of aquatic plants) directly influence the structure and the spatial and temporal variations of several species of Tropisternus.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory demands of some of these genera may be satisfied by a thin layer of air maintained along their body surface (plastron), which makes regular ascents to the water surface, and some others have a respiratory siphon to intake atmospheric oxygen. Gómez Lutz et al (2015) found that the habitats and microhabitats (forming by different species of aquatic plants) directly influence the structure and the spatial and temporal variations of several species of Tropisternus.…”
Section: Discussionmentioning
confidence: 99%